ANALISIS KEPUASAN KONSUMEN PEMBIBITAN BUAH BUAHAN DI KIOS SUKA MAKMUR DESA PEKALONGAN KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Aris Jatmiko; Ismalia Afriani; Kusmaria Kusmaria (Jurnal WACANA PERTANIAN, 2019)
Suka Makmur store is a store that sells fruit seeds in Pekalongan Village. Suka Makmur store provides various types of fruit seeds for sale to consumers. Consumers at the Suka Makmur store are more than compared to other stores because the location is close to the Pekalongan Market. Seed sellers provide services as well as the quality of their products to consumers as a factor that determines whether or not they are satisfied with the fruit nurseries provided by the seller. The purpose of this study was to determine the level of satisfaction of consumers of fruit nurseries.  The results of the study concluded that the level of consumer satisfaction in fruit nurseries in Kios Suka Makmur, Pekalongan Village, Pekalongan District, East Lampung Regency was satisfied. This is involved from the calculation of the Customer Satisfaction index (CSI), that the value of the consumer satisfaction index is 0.71. This value is in the range of satisfaction indexs between 0.66 - 0.80, which means consumers are satisfied with the fruit nurseries provided by fruit seed sellers and are as expected by consumers.